Utility-Scale Solar Photovoltaic Power Plants : A Project Developer’s Guide - International Finance Corporation (Washington, DC, 2015)
With an installed capacity greater than 137 gigawatts (GWs) worldwide and annual additions of about 40 GWs in recent years, solar photovoltaic (PV) technology has become an increasingly important energy supply option. A substantial decline in the cost of solar PV power plants (80 percent reduction since 2008) has improved solar PV’s competitiveness, reducing the needs for subsidies and enabling solar to compete with other power generation options in some markets. The World Bank Group (including the International Bank for Reconstruction and Development, the International Development Association, International Finance Corporation (IFC), and the Multilateral Investment Guarantee Agency) helps client countries secure the affordable, reliable, and sustainable energy supply needed to end extreme poverty and promote shared prosperity. The approach mirrors the objectives of the sustainable energy for all initiative - achieving universal access, accelerating improvements in energy efficiency, and doubling the global share of renewable energy by 2030. The World Bank Group recognizes that each country determines its own path for achieving its energy aspirations, and that each country’s transition to a sustainable energy sector involves a unique mix of resource opportunities and challenges, prompting a different emphasis on access, efficiency, and renewable energy. The objective of this guidebook is to enhance the reader’s understanding of how to successfully develop, finance, construct, and operate utility-scale solar PV power plants. The guidebook focuses on aspects of project development that are specific to solar. From this perspective it covers all aspects of the overall project development process including site identification, plant design, energy yield, permits and licenses, contractual arrangements, and financing, giving sparser coverage to general project development basics that are not specific to solar. This guide covers the key building blocks to developing a successful utility-scale solar power project (the threshold for utility-scale depends on the market, but generally at least 5 megawatt (MW).